Cultural Models of Well-Being Implicit in Four Ghanaian Languages - Osei-Tutu, Annabella; Dzokoto, Vivian A.; Affram, Adjeiwa Akosua; Adams, Glenn; Norberg, Joakim; Doosje, Bertjan (Frontiers in Psychology, 2020)
This contribution to the collection of articles on “African Cultural Models” considers the topic of well-being. Reflecting modern individualist selfways of North American and European worlds, normative conceptions of well-being in hegemonic psychological science tend to valorize self-acceptance, personal growth, and autonomy. In contrast, given the embedded interdependence of everyday life in many West African worlds, one can hypothesize that cultural models of well-being in many Ghanaian settings will place greater emphasis on sustainability-oriented themes of material sufficiency and successful navigation of normative obligations. To explore this hypothesis, we interviewed local cultural experts who function as custodians of religion and an important source of support for well-being in many Ghanaian settings. We asked participants to identify and explain models of well-being implicit in four Ghanaian languages (Akan, Dagbani, Ewe, and Ga). Participants were 19 men and 15 women (age range 32-92 years; Mean=59.83; SD: 14.01). Results reveal some features of local models, including good health and positive affective states, that appear to resonate with standard understandings of well-being in hegemonic psychological science. However, results also provide evidence for other features of local models—specifically, good living (including moral living, material success, and proper relationality) and peace of mind—associated with a sustainability or maintenance orientation to well-being.